Determinants of Graduates' Start‐Ups Creation across a Multi‐Campus Entrepreneurial University: The Case of Monterrey Institute of Technology and Higher Education2. (4th October 2017) - Guerrero, Maribel; Urbano, David; Cunningham, James A.; Gajón, Eduardo
Abstract : Individual and organizational entrepreneurial activity varies across regions/countries. Universities have increasingly become knowledge‐intensive environments that support entrepreneurship. Extant studies demonstrate the need to explore graduate start‐ups using different levels of analysis an across economies. This paper explores individual and university determinants of graduates' start‐ups creation from a multi‐campus entrepreneurial university in a transition economy. A proposed model was tested with 11, 569 graduates from 30 campuses across 21 Mexican cities. Results show that specific individual determinants are the most relevant determinant of graduate entrepreneurship as well as that some university mechanisms (incubators and research parks) have limited impact on graduates' entrepreneurship.